EFFECTS OF JOB SATISFACTION STRATEGIES ON ORGANIZATIONAL COMMITMENT OF ELECTRONIC COMPANIES IN MOGADISHU, SOMALIA - DAHIR AHMED, ABDIRASHID; Gichinga, Dr Lucy (IJRDO - Journal of Business Management, 2016)
The purpose of this research was to examine the effect of job satisfaction strategy on organizational commitment in electronic companies in Mogadishu-Somalia. The study would adopt a quantitative research with the specific research design being a descriptive design. The population of the study is the classified electronic companies located in Bakara market, and they are 15 electronic companies in Bakara market, the employees work that 15 electronic companies are 340 employees. The sampling frame is 340 employees in 15 electronic companies arising from the sample size of 184 employees are extensively survey to ascertain the influence of job satisfaction drivers on their commitment. The sampling technique would use is purposive sampling. Primary data is collect by use of questionnaires which are administering through drop and pick method. Data screening would be done to identify any missing data and it is further taste for reliability and normality. Data would be analyzing using SPSS version 20. Descriptive statistics e.g standard deviations and inferential statistics such as Pearson’s correlation, ANOVA and multiple regression analysis would be used for further analysis. From the findings of the regression analysis, the study found that there was a variation of 94.9% on organizational commitment of electronic companies in Mogadishu due to changes in compensation strategy, promotion strategy, and working environment strategy at 95% confidence interval. This shows the significant that 94.9% of the variati ons in the organizational commitment of electronic companies in Mogadishu are accounted for by the variations in the independent variables and the remaining 5.1% are accounted by other factors contained in the standard error. The study further revealed that there was positive strong relationship between compensation strategy, promotion strategy, and working environment strategy and organizational commitment of change as shown by strong positive correlation coefficient.